"As We Grow, It Will Become a Priority"*: American Mobile Start-Ups' Privacy Practices. (September 2018) - Chen, Wenhong; Huang, Gejun; Miller, Joshua; Lee, Kye-Hyoung; Mauro, Daniel; Stephens, Bryan; Li, Xiaoqian
Privacy has become a crucial issue of the digital age, with significant social, political, and economic ramifications. A growing body of literature has dedicated to the patterns, causes, and consequences of individuals' privacy concerns, skills, and practices. Advancing a producer's perspective, this research draws on in-depth interviews with 45 tech entrepreneurs to examine privacy practices of mobile start-ups in the United States. Results reveal (a) factors that contribute to the problematic status of privacy issues and (b) whether and how entrepreneurs leverage privacy management as a competitive advantage. Results show that data are widely seen by entrepreneurs as a potentially profitable asset. Privacy practices are networked and thus pose challenges for privacy management as different parties may have different privacy practices. Fast-moving technologies often leave government regulations behind, making them look outdated or irrelevant to many entrepreneurs. For most start-ups not specialized in identity, privacy, or anonymity service, privacy is neither a core business strategy nor a top concern. Only a few mobile ventures have leveraged privacy management as a competitive advantage and designed their products from the ground up concerned about privacy. Most entrepreneurs adopt a building-the-plane-while-flying-it approach: as business grows, privacy policies and practices would evolve. Many entrepreneurs fail to recognize the significance of privacy policies and practices as they lack the awareness, bandwidth, and capacity. Growth and monetization pressures from investors are perceived as more urgent and important than privacy and security issues. Offering a richer account of the power structure that shapes mobile entrepreneurs' privacy practices and their challenges of managing privacy in a data-driven digital economy, our work advances the existing literature dominated by stories of the individual consumers.